Foetal Venous Anomalies: Experience in a Primary Referral Unit - Chaudhary, Yogeshkumar S.; Patil, Sachin Shridhar (Journal of Fetal Medicine, 2020)
Congenital heart disease (CHD) is one of the most common congenital anomalies reported. Incidence of CHD is 8 to 9 per 1000 live births in published data worldwide (Chaudhary and Patil in J Fetal Med 5:221, 2018; Hoffman and Kaplan in J Am Coll Cardiol 39(12):1890–1900, 2002; Khalil et al. in Indian Pediatr 31(5):519–527, 1994; Wanni et al. in Heart India 2(3):76–95, 2014). Association of venous anomalies is known and has a significant impact on the perinatal and postnatal outcome. There is no published data about the incidence and spectrum of foetal venous anomalies in India. We tried to find out the incidence and spectrum of foetal venous anomalies in second and third trimester low risk population during routine ultrasound examination in our primary referral unit. 61 foetuses out of 19,929 were found to have venous anomalies with an incidence of 3 per 1000 s and third trimester pregnancies. Persistent left superior vena cava was the most common anomaly seen followed by umbilical vein varyx and absent ductus venosus. 46% of cases showed associated cardiac and extracardiac anomalies.
Keywords: Ultrasound (US) examination; Foetal venous anomalies; Incidence and spectrum; India